Photocatalytic desulfurization of thiophene under visible light by hollow flower-like NixZn2-xV2O7/WO4 nanostructures. Issue 19 (1st October 2021) - Siahmansouri, Mahvash; Mousavi-Kamazani, Mehdi
Abstract: In order to improve the desulfurization efficiency of petroleum derivatives, this paper reports the synthesis and characterization of hollow flower-like Nix Zn2-x V2 O7 /WO4 nanostructures through a simple Pechini sol-gel method. The type of chelating agent, gelling agent, and elements ratio were investigated as factors affecting morphology to determine the optimal conditions. SEM images showed that if all the elements Ni, Zn, V, and W were involved in the formation of the product, hollow flower-like nanostructures with a high surface area were formed while in the absence of any of these elements the morphology changed. Good morphology and high adsorption efficiency along with ultra-light absorption according to DRS, resulted in more than 95% efficiency of photocatalytic oxidative desulfurization after 2.5 hours under visible light. The reduction in efficiency from 95% to 23% in the presence of EDTA indicated that superoxide was the most active radical species in the process. Comparison of the performance of Zn2 V2 O7 /ZnWO4, Ni2 V2 O7 /NiWO4, NiZnWO4, and NiZnV2 O7, which were 66%, 69%, 84% and 63%, respectively, showed the effect of the type of composition in addition to morphology.